2023
DOI: 10.3389/fimmu.2023.1135096
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune pancreatitis: A bibliometric analysis from 2002 to 2022

Abstract: Background/ObjectivesAutoimmune pancreatitis (AIP) is a distinct form of pancreatic inflammatory disease that responds well to glucocorticoid therapy. Knowledge on AIP has rapidly evolved over the past two decades. Based on bibliometric analysis, this study aimed to assess the research status of AIP over the past two decades and determine the research focus and emerging topics.MethodsAIP-related publications published between January 1, 2002, and June 6, 2022, were retrieved from the Web of Science Core Collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Keyword burst detection is a useful tool for identifying research frontiers and emerging topics in a particular field over time. 22 A burst keyword is one that appears frequently in a given period of time, providing insight into the evolution of research hotspots and trends. To gain a better understanding of the development of electrochemical biosensor research, the top 25 keyword terms with the strongest emergent strength analysed from 2003 to 2023 are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Keyword burst detection is a useful tool for identifying research frontiers and emerging topics in a particular field over time. 22 A burst keyword is one that appears frequently in a given period of time, providing insight into the evolution of research hotspots and trends. To gain a better understanding of the development of electrochemical biosensor research, the top 25 keyword terms with the strongest emergent strength analysed from 2003 to 2023 are illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TRPA1 is the only member of the TRPA subfamily of mammalian TRP channels [ 46 ]. However, differences in the structure of TRPA1 have been verified between species, with mammals expressing only one functional TRPA1, while four functional TRPA1s have been identified in drosophila [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is now widely used in medical fields, such as orthopedics, autoimmune diseases, etc. [ 15 17 ] However, no bibliometric studies on wrist arthroscopy have been found in recent years. Therefore, in this study, we utilized sophisticated bibliometric tools, including CiteSpace, [ 18 ] VOSviewer, [ 19 ] R package“Bibliometrix,” [ 20 ] and an online analysis platform ( https://bibliometric.com ), to obtain comprehensive data on references related to wrist arthroscopy literature.…”
Section: Introductionmentioning
confidence: 99%